Individual, contextual, and social network factors affecting exposure to HIV/AIDS risk among older residents living in low-income senior housing complexes. - Schensul, Jean J; Levy, Judith A; Disch, William B (Journal of acquired immune deficiency syndromes (1999), 2003)
This study examines the influence of individual, contextual (building location and characteristics), and social network characteristics on HIV prevalence and risk behavior among people older than 50 years of age living in low-income senior housing in two cities, Hartford, Connecticut and Chicago, Illinois. The authors' study focuses on older residents of six buildings located in impoverished neighborhoods with high rates of HIV transmission through injection drug use and unprotected sexual activity, including the exchange of sex for drugs and money. The article is organized into three sections. First, the authors explore the HIV prevalence, distribution, and risk behaviors that may contribute to new infections among the buildings' older residents in general. These practices include unprotected sexual intercourse, sex with commercial sex workers, casual or multiple partners, regular use of alcohol and/or illicit drugs, and other high-risk activities that expose older residents to HIV, sexually transmitted diseases, and other negative health consequences. Next, the authors examine the relationship between building and neighborhood characteristics, the internal social organization of buildings, and the risk behaviors of individual residents by building residency. Finally, the authors use a social network analysis to identify possible entry points and transmission routes for HIV infection through drug and sexual exchanges between and among building residents and visitors. This approach also reveals variations in building structures that may facilitate the diffusion of HIV prevention efforts.
Keywords: Acquired Immunodeficiency Syndrome; Aged; Chicago; Connecticut; Female; HIV Infections; Housing for the Elderly; Humans; Male; Marital Status; Poverty; Risk Assessment; Risk-Taking